Asuransi Syariah dalam Menopang Pemulihan Ekonomi Berdasarkan Undang-Undang Nomor 40 Tahun 2014 Tentang Perasuransian - Karso, A. Junaedi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
In Indonesia, there is unit-linked sharia insurance. The governance of Islamic financial instruments tends to be considered better than conventional instruments. The sharia principle is the principle of Islamic law in insurance activities based on fatwas issued by institutions that have authority in determining fatwas in the field of sharia. Based on Law Number 40 of 2014, sharia insurance is a collection of agreements, consisting of agreements between sharia insurance companies (tijarah  or buying and selling contracts) and policyholders as well as agreements between policyholders (tabarru' or social funds), in the context of contribution management. The basic principle of Islamic finance is that the economy of the people involves the participation of as many people as possible. "In the midst of the Covid-19 pandemic, investors tend to choose instruments that are safe from turmoil". Sharia insurance is an insurance model that follows the principles of sharia law (Islam) also known as takaful, where customers as insurance participants contribute with the tabarru' contract to help each other among participants who face disasters, or it can be said to be a risk sharing concept  among participants. Sharia insurance runs within the framework of sharia law, which prohibits transactions by charging interest (riba), engaging in speculative transactions (gharar), and investing in morally and socially detrimental businesses (haram). Types of sharia insurance, namely: (1). Life Insurance; (2). Health Insurance; (3). Property Insurance; (4). Motor Vehicle Insurance; (5). Travel Insurance; (6). Sharia health insurance. The concept of sharia insurance: (1). Help through the concept of ta'awun by forming a collective fund for the common good; (2). Protect each other through the concept of takaful by providing protection in the form of compensation, reimbursement, or payment for the occurrence of a certain risk. Sharia insurance can help manage risks, namely: (1). Anticipation of various risks should be identified in advance; (2). Participation in insurance should be in accordance with the needs and financial capabilities of each individual; (3). Forming an investment fund for future plans.